Effect of Delayed Light-Curing Through a Zirconia Disc on Microhardness and Fracture Toughness of Two Types of Dual-Cure Cement - Pouran Samimi; Sara Kaveh; Maryam Khoroushi (Tehran University of Medical Sciences, 2018)
Objectives: Photopolymerization immediately sets dual-cure cements and prevents the continuation of chemical polymerization. Delayed light-curing allows the chemical process to continue up to the point before starting irradiation; however, there is a controversy in this respect. The present study evaluates the effect of delayed light-curing through a zirconia disc on the microhardness and fracture toughness (KIC) of two types of dual-cure cement. Materials and Methods: Samples measuring 25×5×3 mm3 were prepared for fracture toughness test, and discs measuring 5 mm in diameter and 3 mm in thickness were prepared for microhardness test using Bifix and BisCem cements. Light-curing protocols were as follows: immediate light-curing (group A), a 2-minute delay (group B), a 5-minute delay (group C), direct irradiation (group D), and no irradiation (group E). In groups A to C, light-curing was carried out through a zirconia disc. Data were analyzed by two-way and one-way analysis of variance (ANOVA), post-hoc Tukey's test, and Kruskal-Wallis test at 95% confidence interval. Results: There was a significant difference in the microhardness of the cements (P=0.00). Delayed light-curing had no effect on microhardness (P=0.080). The microhardness of BisCem in group E was significantly lower than that in group D (P=0.015). The fracture toughness of Bifix in groups B and C was significantly different than that in group E and BisCem groups. Conclusions: Under the limitations of our study, delayed light-curing had different effects on microhardness and fracture toughness. Differences in light-curing protocols resulted in different effects based on the cement type. Light-curing is recommended to achieve optimal mechanical properties.